PENGARUH FREE CASH FLOW, LEVERAGE, PRICE EARNINGS RATIO, DAN DIVIDEND TERHADAP STOCK REPURCHASE PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA UNTUK TAHUN 2010-2014 - Octaviani, Lolita; Yulia, Aida (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2017)
The purpose of this study is to examine the effect of free cash flow, leverage, price earnings ratio and dividend on stock repurchase atmanufacturing companies listed on Bursa Efek Indonesia in the period of 2010 to 2014. Dependent variable used in this study is stock repurchase, while independent variables used in this study are free cash flow, leverage, price earnings ratio, and dividend. This study using purposive sampling method, of the companies listed on Bursa Efek Indonesia, 10 companies are selected to be sample in this study.The data used in this research is secondary data obtained from annual reports and financial statements. Data were analyzed using statistical analysis, the multiple linear regression analysis. Then the data is processed usingthe statistical package for social science (SPSS) 22.The results of this study indicate thatfree cash flow, leverage, price earnings ratio, and dividendjointly affectthe stock repurchase. Free cash flow and price earnings ratio have significant positive effect on stock repurchase, while leverage and dividend have significant negative on the stock repurchase.Keywords: Free Cash Flow, Leverage, Price Earnings Ratio, Dividend, Stock Repurchase.